2010
DOI: 10.2174/1874924001003010080
|View full text |Cite
|
Sign up to set email alerts
|

Shelter from the Storm: Trauma-Informed Care in Homelessness Services Settings

Abstract: It is reasonable to assume that individuals and families who are homeless have been exposed to trauma. Research has shown that individuals who are homeless are likely to have experienced some form of previous trauma; homelessness itself can be viewed as a traumatic experience; and being homeless increases the risk of further victimization and retraumatization. Historically, homeless service settings have provided care to traumatized people without directly acknowledging or addressing the impact of trauma. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
176
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(182 citation statements)
references
References 40 publications
(23 reference statements)
4
176
0
2
Order By: Relevance
“…How do we amplify the inclusionary bonding service users expressed towards one another despite identity differences? Emerging discourses of traumainformed care (TIC) in homeless services aim to create safer spaces and ensure that diversity amongst users is addressed and respected (Hopper et al, 2010). Open door policies promote TIC's inclusionary approach to diversity, requiring service providers to practice openness and engage with the diversity of service users.…”
Section: Discussionmentioning
confidence: 99%
“…How do we amplify the inclusionary bonding service users expressed towards one another despite identity differences? Emerging discourses of traumainformed care (TIC) in homeless services aim to create safer spaces and ensure that diversity amongst users is addressed and respected (Hopper et al, 2010). Open door policies promote TIC's inclusionary approach to diversity, requiring service providers to practice openness and engage with the diversity of service users.…”
Section: Discussionmentioning
confidence: 99%
“…These findings collectively suggest that future research with PEH should be aimed at addressing trauma informed care. Trauma informed care encompasses services that recognize the impact of trauma on the lives of PEH by emphasizing collaboration, choices, and client strengths through respectful, consistent health, and social care (Hopper et al, 2010). Further support for the exploration of trauma informed care in homeless services was provided by the strong inverse relationship between QoL and substance use among PEH (Magee et al, 2019;O'Brien et al, 2015;Stergiopolous et al, 2014) and the reported high rates of substance use among PEH in highincome countries (Fazel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One approach recommended in clinical guidelines is trauma-informed care. [18][19][20] The Substance Abuse and Mental Health Services Administration has defined trauma-informed care as a programme, organisation, or system that realises the widespread impact of trauma and understands potential paths for healing; recognises the signs and symptoms of trauma in staff, clients, and others involved with the system; and responds by fully integrating knowledge about trauma into policies, procedures, practices, and settings. 21 In 2010, Hopper 18 described the four core principles of trauma-informed care in homeless services as trauma awareness, safety, choice and empowerment and a strengths-based approach.…”
Section: Open Accessmentioning
confidence: 99%
“…[18][19][20] The Substance Abuse and Mental Health Services Administration has defined trauma-informed care as a programme, organisation, or system that realises the widespread impact of trauma and understands potential paths for healing; recognises the signs and symptoms of trauma in staff, clients, and others involved with the system; and responds by fully integrating knowledge about trauma into policies, procedures, practices, and settings. 21 In 2010, Hopper 18 described the four core principles of trauma-informed care in homeless services as trauma awareness, safety, choice and empowerment and a strengths-based approach. The National Centre on Family Homelessness outlined several reasons why programmes need to be trauma informed, 22 including that trauma can impact how people access services, including viewing people and services as unsafe; recognition that people adapt to trauma to keep themselves safe including abusing substances, becoming aggressive, or withdrawing; and, programmes and services cannot be 'one size fits all'.…”
Section: Open Accessmentioning
confidence: 99%